2004
DOI: 10.1161/01.atv.0000143855.85343.0e
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Shear Stress and Circumferential Strain Reduces Endothelial NO Synthase and Cyclooxygenase-2 but Induces Endothelin-1 Gene Expression in Endothelial Cells

Abstract: Objective-Endothelium-derived vasoactive agents NO, endothelin-1 (ET-1), and prostacyclin (PGI 2 ) not only regulate vascular tone but also influence atherogenic processes, including smooth muscle migration and proliferation, as well as monocyte and platelet adhesion. Complex hemodynamics characterized by the temporal phase angle between mechanical factors circumferential strain and wall shear stress (stress phase angle [SPA]) have been implicated in regions prone to pathologic development, such as atheroscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 43 publications
(47 reference statements)
4
77
0
Order By: Relevance
“…How perfusion pressure increases CD ET-1 production is speculative, although one possibility is tubule flow rate; shear stress increases endothelial cell ET-1 production. 25,26 Two other aspects of the pressure-excretion studies deserve comment. First, the BP difference between CD ET-1 KO and control mice was abolished by isoflurane anesthesia.…”
Section: Schneider Et Al Collecting Duct Et-1 Affects Blood Pressure mentioning
confidence: 99%
“…How perfusion pressure increases CD ET-1 production is speculative, although one possibility is tubule flow rate; shear stress increases endothelial cell ET-1 production. 25,26 Two other aspects of the pressure-excretion studies deserve comment. First, the BP difference between CD ET-1 KO and control mice was abolished by isoflurane anesthesia.…”
Section: Schneider Et Al Collecting Duct Et-1 Affects Blood Pressure mentioning
confidence: 99%
“…2,5,6 The coronary artery is characterized by asynchronous hemodynamics, wherein the wall shear stress from blood flow is out of phase with the circumferential strain from blood pressure 105 and this may play a role in determining the heterogeneous eNOS expression in the coronary arterial tree. 106,107 Further support for the role of hemodynamics in eNOS protein expression comes from studies in miniature swine following prolonged aerobic exercise training. 108 Following weeks of training, eNOS protein content was increased by over 50% in coronary arteries and small and large arterioles, but unaltered in coronary conduit and intermediate arterioles, 108 suggesting that steady state adaptations to exercise hemodynamic stimuli include nonuniform changes in eNOS expression that lead to an NO-mediated improvement in coronary resistance artery endothelium-dependent dilation.…”
Section: Heterogeneity Of Enos Expression In the Coronary Vascular Bedmentioning
confidence: 99%
“…It has been shown that endothelial CAM expression can be modulated by mechanical stimuli, which is recognized through stress-sensitive promoter elements (13). Hemodynamic forces, such as fluid shear stress, are known to regulate vascular wall structure/function including EC cell shape, nitric oxide and prostacyclin production, EC proliferation, and CAM expression (2,3,7,20). Studies have demonstrated that exposure of EC to normal laminar flow patterns produces low levels of CAM and enhances the production of antiadhesive factors (17,20).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that exposure of EC to normal laminar flow patterns produces low levels of CAM and enhances the production of antiadhesive factors (17,20). However, when EC are exposed to altered patterns of flow, CAM expression/production significantly increases (7,20). This perturbed flow-induced increase in CAM expression/ production can then become the trigger for inflammation.…”
Section: Discussionmentioning
confidence: 99%